Teacher-entrepreneurialism: a case of teacher identity formation in neoliberalizing education space in contemporary India. Issue 4 (8th August 2021) - Gupta, Achala
ABSTRACT: This article examines the processes underlying the formation of the identity of teachers as entrepreneurs in neoliberalizing education space in contemporary India. Drawing on interactions with 38 schoolteachers in two private schools in Dehradun, this article explores why and how educators adopt specific entrepreneurial strategies to navigate precarious, competitive market conditions. It subsequently illustrates how, in their pursuit of career advancement, educators commodify their knowledge and skills and promote the market logic of choice and freedom. By elucidating the mechanisms through which educators reproduce the processes and practices that nudge their search for promising career opportunities in the formal education system and the tuition industry, this article argues that teacher-entrepreneurs are both products and carriers of the neoliberal agenda. It introduces the concept of teacher-entrepreneurialism, a manifestation of neoliberalism, which shapes educators' entrepreneurial dispositions; it suggests that teacher-entrepreneurs sustain neoliberalization in its varying forms and bolster its legitimacy. By illustrating the variegated, processual existence of neoliberalism, this article makes a case for investigating education as a neoliberalizing space in the increasingly profit-centric, market-driven, and performance-oriented schooling sector that prevails across societies, particularly in contemporary India.